A review of smart contract blockchain based on multi-criteria analysis: challenges and motivations - Alamoodi, Abdullah Hussein (Tanjung Malim, 2023)
A review of smart contract blockchain based on multi-criteria analysis: challenges and motivations by Alamoodi, Abdullah Hussein